CFD Analysis Of Flue Gas Streamline Through Varied Of Flow Straightener Inclination - Pramadhony Pramadhony; Dewi Puspitasari; Ellyanie Ellyanie; Marwani Marwani; Rizki M. R. Sihombing (Indonesian Journal of Environmental Management and Sustainability, 2018)
Air emission, generated by industrial sector, is one of the main contributors of ambient air quality degradation. In order to minimize the impact to its surrounding, the company regularly should conduct an air emission monitoring activity by measuring the hazardous compound concentration. The sample should be taken in a reference plane located two diameter from the outlet. The sampling of air emission by using isokinetic method cannot be conducted when the swirling flow is existed; the streamline is also should be uniform and vertical. Flow straightener with difference inclination angles, 0°, 15°, and 30°, are suggested to condition the streamline and fulfill the requirements. A computational simulation conditions with no flow straightener and with three flow straighteners are conducted to overview the influence of flow straightener inclination. Based on the analysis these inclinations are effectively improving the uniformity of velocity at reference plane. In other side these inclinations are causing the increasing of helicity as well as streamline inclination